KOMPYUTER LINGVISTIKASIDA AUDIOKORPUS MASALALARI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article analyzes a corpus created using modern computer technologies and several ideas for improving its capabilities. Foreign experience in creating audio-text corpora of the electronic corpus of the Uzbek language has been studied, and attention has also been paid to the practical aspects of including oral speech acts in the corpus database.
Keywords: computational linguistics, electronic corpus, audio corpus, multimedia corpus, Uzbek language.